Managerial Ownership, Firm Size, Liquidity, and Capital Intensity as Determinants of Tax Avoidance: Evidence from Manufacturing Firms in Indonesia - Riedwan Adhie Saputra; Lulus Kurniasih (Best Journal of Administration and Management, 2025)
Tax avoidance is a critical issue in corporate governance, especially in emerging economies where tax revenues are vital for state financing. This study investigates the influence of managerial ownership, firm size, liquidity, and capital intensity on tax avoidance among manufacturing firms listed on the Indonesia Stock Exchange (IDX) during 2019–2023. Using purposive sampling and secondary data from 595 firm-year observations, tax avoidance is measured by the Effective Tax Rate (ETR) and analyzed with panel regression under the Random Effect Model, supported by robust tests. The results show that capital intensity has a significant effect on tax avoidance, while managerial ownership, cash ratio, and firm size are not significant. These findings highlight the role of asset structure in shaping corporate tax strategies and contribute to the literature within agency, political cost, pecking order, and tax shield frameworks, while offering practical insights for policymakers and managers.